Method of solving the problem of finding hypothetically connected objects - Chetverikov, G. G.; Vechirska, I. D. (ХНУРЭ, 2011)
In work the basic aspects of mathematical modeling of AFP – structures (as nanostructures) on the basis of decomposition of multiple-valued structures are investigated, also there have been investigated an approach to the implementation of the linear logical transformation finding method for solving hypothetically connected subscribers problem in the automated system of complex calculations of telecommunication enterprise.
Keywords: nanostructures; automated system; telecommunication